Evaluation of employees in public day care centers knowledge about breastfeeding and complementary feeding - Joelânia Pires de O. Souza; Amanda Moura Prudente; Dyene Aparecida Silva; Leandro Alves Pereira; Ana Elisa M. Rinaldi (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To evaluate the knowledge of public day care centers employees about breastfeeding and complementary feeding. METHODS: A cross-sectional study was conducted in 15 public day care centers randomly selected in the city of Uberlandia, Southeast Brazil. A questionnaire applied to school principals, teachers, educators and general services assistants (GSA) included demographic and socioeconomic variables and questions about knowledge on breastfeeding, complementary feeding besides employees' perceptions about these subjects. Kruskal-Wallis with multiple comparison and chi-square tests were used to compare variables by professional category. RESULTS: 304 employees participated in the study. The highest percentages of correct answers were noted for questions about exclusive breastfeeding: definition - 97% (n=296) and duration - 65% (n=199). Regarding complementary feeding, 61% (n=187) correctly answered about the appropriate age to introduce it, with a lower percentage for meat (56%; n=170) and sugar (16%; n=50). Concerning employees' perceptions, 9% (n=29) believed that there is weak breast milk, 79% (n=241) and 51% (n=157) reported the negative influence of bottle feeding and pacifier use on breastfeeding. Among the interviewed subjects, 77% (n=234) answered that they had a positive influence on the quality of the food given to the children. There were no differences in the answers according to professional category, except for the negative influence of pacifiers on breastfeeding. CONCLUSIONS: Employees of public day care centers knew more about breastfeeding than about complementary feeding. Educational activities about breastfeeding and complementary feeding are necessary for day care centers employees.